2014
DOI: 10.3892/or.2014.3043
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation inhibition and differentiation induction of hepatic cancer stem cells by knockdown of BC047440: A potential therapeutic target of stem cell treatment for hepatocellular carcinoma

Abstract: Recent findings suggest that clinical hepatocellular carcinoma (HCC) progression is driven by hepatic cancer stem cells (HCSCs) through their capacity for self-renewal, generation of heterogeneous lineages of cancer cells, resistance to chemotherapy and their ability to divide limitlessly, which may contribute to the failure of existing therapies to consistently eradicate malignant tumors. Therefore, HCSC-directed therapeutic approaches might represent strategies to improve clinical HCC therapy. In previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Therefore, HCSC-directed therapeutic approaches might represent strategies to improve clinical HCC therapy [78]. Future studies might aim to determine whether lncRNA is involved in maintaining HCSC malignant behavior (including proliferation and differentiation).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, HCSC-directed therapeutic approaches might represent strategies to improve clinical HCC therapy [78]. Future studies might aim to determine whether lncRNA is involved in maintaining HCSC malignant behavior (including proliferation and differentiation).…”
Section: Discussionmentioning
confidence: 97%
“…An all-trans retinoic acid was combined with conventional chemotherapy and used to treat patients with acute promyelocytic leukaemia, with successful induction of differentiation [110,111]. Recent studies have demonstrated that induction of differentiation of hepatic carcinoma stem cells by down-regulation of BC047440 (a gene involved in cancer growth and proliferation) suppressed the tumorigenic potential of hepatic carcinoma stem cells both in vivo and in vitro [112,113]. Also, Zieker and co-workers reported the induced differentiation of gastric carcinoma stem cells (CD44þ cells) by knocking-down phosphoglycerate kinase 1 (a metabolic enzyme responsible for cancer cell invasion and dissemination) using shRNA.…”
Section: Approaches In Targeting Cscsmentioning
confidence: 98%
“…Inhibit the switching of stem cell like properties of cancer cells and prevent CSC generation [200][201][202] Differentiation Switching on metabolic pathways associated with cell maturation Make the CSCs more sensitive to conventional therapies and killed them completely [112][113][114][115] Metabolic pathways…”
Section: Approaches In Targeting Cscsmentioning
confidence: 99%
“…The process of transformation of HCC cells to hepatocellular carcinoma stem cells (HCSCs) is associated with the initiation, progression, metastasis and poor prognosis of HCC (21,22).…”
Section: Discussionmentioning
confidence: 99%